Intercultural adaptation and influencing factors analysis of the Chinese version of the anxiety scale for the older adults in a long-term care population - Feng, Fuzhe; Chen, Qing; Zheng, Chen; Zhang, Huijun (Frontiers in Public Health, 2023)
Objective The purpose of this study was to translate the Geriatric Anxiety Scale-Long-Term Care into Chinese and to assess its reliability and validity in a long-term care population, as well as to explore factors contributing to anxiety in older adults requiring long-term care. Methods The study recruited 399 older adults residents requiring long-term care and used the Brislin double translation-back-translation method to create the initial Chinese version of the Geriatric Anxiety Scale-Long-Term Care. The study used internal consistency and split-half reliability to assess the reliability of the scale, as well as exploratory factor analysis, validation factor analysis, and content validity to assess the validity of the scale. Linear regression was used to analyze the relationship between the independent variables and anxiety levels in the long-term care population. Results The Cronbach’s coefficient value of the Chinese version of the Geriatric Anxiety Scale-Long-Term Care was 0.81, and the split-half reliability was 0.80. The results of exploratory factor analysis showed support for a one-dimensional factor structure. The results of the validation factor analysis indicated a good fit for the one-factor model. Gender (β = 0.190, 95% CI:0.540 ~ 1.546, p < 0.001), self-rated health (β = 0.220, 95% CI:0.379 ~ 0.953, p < 0.001), life satisfaction (β = −0.315, 95% CI: −1.355 ~ −0.734, p < 0.001) and participation in activities (β = −0.106, 95% CI: −1.122 ~ −0.084, p < 0.05) were significant predictors of anxiety levels in the long-term care population. Conclusion The Chinese version of the Geriatric Anxiety Scale-Long-Term Care has good reliability and validity in the long-term care population. The Geriatric Anxiety Scale-Long-Term Care is effective in assessing the anxiety level of the Chinese long-term care older adults population and provides an opportunity to detect and observe anxiety disorders in the long-term care population.